Determinants of Competitive Antagonist Sensitivity on Neuronal Nicotinic Receptor β Subunits - Harvey, Scott C. (J Neurosci, 1996)
We constructed a series of chimeric and mutant neuronal nicotinic acetylcholine receptor β subunits to map amino acid residues that determine sensitivity to competitive antagonists. The β2 and β4 subunits form pharmacologically distinct receptors when expressed in combination with the α3 subunit in Xenopus oocytes. At equipotent acetylcholine concentrations, α3β2 is 56-fold more sensitive to blockade by dihydro-β-erythroidine than is α3β4. The α3β2 combination is also sensitive to long-term blockade by neuronal bungarotoxin, whereas α3β4 is not. Pharmacological analysis of receptors formed by chimeric β subunits reveals that amino acid residues that determine both dihydro-β-erythroidine and neuronal bungarotoxin sensitivity are located within several sequence segments. The major determinant of sensitivity to both competitive antagonists is located between residues 54 and 63. A minor determinant of sensitivity to both antagonists lies between residues 1 and 54, whereas a minor determinant of NBT sensitivity lies between residues 74 and 80. Within region 54–63 of β2, mutant β2 subunits were used to identify threonine 59 as a residue critical in determining competitive antagonist sensitivity. Changing threonine 59 to lysine, as occurs in β4, causes a 9-fold decrease in dihydro-β-erythroidine sensitivity and a 71-fold decrease in neuronal bungarotoxin sensitivity. Changing polar threonine 59 to negatively charged aspartate causes a 2.5-fold increase in neuronal bungarotoxin sensitivity and has no effect on dihydro-β-erythroidine sensitivity.